Manajemen Pemasaran Bibit Alpukat Di CV Wana Gemilang Kabupaten Magelang Jawa Tengah: Marketing Management of Avocado Seeds in CV Wana Gemilang, Magelang Regency, Central Java - Widiyantono, Didik; Haryanti, Haryanti (Jurnal Riset Agribisnis dan Peternakan, 2024)
Avocado seeds are seeds that are quite in demand in the nursery world because of the large number of consumers. In addition, avocado seedlings are also easy to care for. The objectives of this study are: Identifying marketing management of CV Wana Gemilang, Knowing the effectiveness of online and offline marketing of avocado seeds in CV Wana Gemilang,   Knowing how to increase sales profits of avocado seeds in CV Wana Gemilang. Data analysis used to discuss marketing management descriptively is an analysis method based on solving actual problems that exist today. Application of Marketing Management in CV. Wana Gemilang. Avocado Seed Marketing Planning Stage, Organizing, Implementing Avocado Marketing  in CV. Wana Gemilang. Online and Offline Marketing Strategies.   Increased profit from sales.  There are two ways to do marketing strategies in CV wana Gemilang, namely offline and online. Offline marketing is still predominantly done because of customer satisfaction factors because they choose their own avocado seeds. Online marketing is carried out using a Whatsapp account only so that promotion is still lacking, but even so there are still many customers who place orders via whatsapp. CV Wana Gemilang's profit in February amounted to Rp8,857,500.00. The increase in sales experienced by CV Wana Gemilang in January to March was as much as 30%.